Establishment of a Radioimmunoassay Service for the Management of Endemic Goitre - AMOUSSOU-GUENOU, KUASSI MARCELLIN (My University, 2007)
Project BEN/6/002 : The objective was to establish in vitro nuclear medicine techniques for detection and management of endemic goitre